Physical Condition Profile of Students Participating in the Futsal Extracurricular Activity at SMP IT As Syakur in Bengkulu City - Erfin Agus Salim; Roni Syaputra; Azizatul Banat (Educative Sportive, 2026)
This study aims to determine the physical condition of students participating in the futsal extracurricular program at SMP IT As Syakur in Bengkulu City. This is aquantitative descriptive study that uses a survey method, and data collection techniques involve tests and measurements. The results of this study are based on physical condition tests of students participating in the futsal extracurricular program at SMP IT As Syakur. The results of the physical condition tests of students participating in the futsal extracurricular program at SMP IT As Syakur in Bengkulu City, conducted on 17 players, are as follows: the “very good” category had 0 (0%) students, the “good” : 0 players (0%); the moderate category: 11 players (65%); the poor category: 6 players (35%); and the very poor category: 0 (0%). Based on the results above, it can be concluded that the overall physical fitness test results for students participating in the futsal extracurricular program at SMP IT As Syakur in Bengkulu City, conducted on 17 players, show that 11 players (65%) fall into the moderate category.